2021
DOI: 10.1177/02698811211032439
|View full text |Cite
|
Sign up to set email alerts
|

Mice lacking melatonin MT2 receptors exhibit attentional deficits, anxiety and enhanced social interaction

Abstract: Background: Aside from regulating circadian rhythms, melatonin also affects cognitive processes, such as alertness, and modulates the brain circuitry underlying psychiatric diseases, such as depression, schizophrenia and bipolar disorder, via mechanisms that are not fully clear. In particular, while melatonin MT1 receptors are thought primarily to mediate the circadian effects of the hormone, the contribution of the MT2 receptor to melatonin actions remains enigmatic. Aims: To characterise the contribution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 83 publications
0
16
0
Order By: Relevance
“…An interesting thing was that several hub genes were involved in the neurological or psychiatric function or disorders such as CHRM4 [70,71], MTNR1B [72], and TAS2R19 [73,74]. Just as reported, plentiful common proteins and biochemical characteristics were shared between the human brain and testis [75].…”
Section: Discussionmentioning
confidence: 84%
“…An interesting thing was that several hub genes were involved in the neurological or psychiatric function or disorders such as CHRM4 [70,71], MTNR1B [72], and TAS2R19 [73,74]. Just as reported, plentiful common proteins and biochemical characteristics were shared between the human brain and testis [75].…”
Section: Discussionmentioning
confidence: 84%
“… 159 An alternative approach, highlighted by work in rodents, would be fMRI and electroencephalographic strategies for exploring circuits involved in the relief of GAD by agomelatine in comparison to other classes of agent. 85 , 108 , 112 , 160 …”
Section: General Discussion: Open Questions and Perspectivesmentioning
confidence: 99%
“… 102 In line with this work, male and/or female mice genetically deprived of MT 2 receptors display enhanced anxiety. 105 108 As regards human subjects, data are very sparse, yet there is fragmentary evidence for anxiolytic effects of MT under specific conditions, such as pre-operative stress. 100 , 109 …”
Section: A Complementary Role For Mt Receptors In the Anxiolytic Acti...mentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the MT2 receptor plays a role in cognition and modulates anxiety and social interactions. Their data provide useful insights into the functions of endogenous melatonin, which may help to inform future drug development strategies focussed on the MT2 receptor (Thomson et al, 2021).…”
mentioning
confidence: 99%